Direct Growth of Carbon Nanotubes Doped with Single Atomic Fe–N4 Active Sites and Neighboring Graphitic Nitrogen for Efficient and Stable Oxygen Reduction Electrocatalysis. (12th September 2019) - Xia, Dongsheng; Yang, Xin; Xie, Lin; Wei, Yinping; Jiang, Wulv; Dou, Miao; Li, Xuning; Li, Jia; Gan, Lin; Kang, Feiyu
Abstract: Single atomic Fe–N x moieties embedded on a high surface area carbon (Fe–N/C) represents one of the most promising nonprecious metal electrocatalysts for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells. While significant progress has been made in the preparation of Fe–N/C catalysts with high‐density Fe–N x sites, key structural descriptors determining the intrinsic activity of the Fe center remain elusive, and effective ways to enhance the intrinsic activity are still lacking. Moreover, most Fe–N/C catalysts developed to date are built on carbons with rather low graphitization degree, which suffer from relatively severe carbon corrosion and thereby poor stability. The direct growth of carbon nanotubes doped with high‐density Fe–N x sites neighbored with graphitic‐nitrogen‐rich environment is reported here, which are successfully applied as a both active and stable ORR electrocatalyst in fuel cells. Combining both experiments and density functional theory calculations, it is revealed that the neighboring graphitic nitrogen can effectively induce higher filling degree of d‐orbitals and simultaneously decrease on‐site magnetic moment (namely, lowered spin) of the Fe center, which can optimize the binding energies of ORR intermediates and thereby substantially enhance intrinsic ORR activity. Abstract : Atomic Fe–N4 active sites with neighboring graphitic nitrogen are successfully doped in carbon nanotubes and demonstrate superior electrocatalytic activity and stability for the oxygen reduction reaction (ORR) in proton‐exchange‐membrane fuel cells. The neighbouring graphitic nitrogen results in a higher filling degree of the d‐orbitals and thus lowered spin of the Fe center, which optimizes the binding energies of ORR intermediates.